After the Plague: Revisiting Experiential and Adventure Education Outcome Variables After Covid-19. (June 2021) - Ewert, Alan; Davidson, Curt
Background : The Covid-19 pandemic has changed the way the world works and experiential and adventure education programs are no exception. These changes have significantly affected various outdoor adventure and experiential education (OAEE) programs and will continue to do so in the foreseeable future.Purpose : To explore changes in outcome variables that may be appropriate for OAEE programs to consider, both during and after the pandemic.Methodology/Approach : Using relevant research literature, outcome variables applicable to a post-pandemic society are identified.Findings/Conclusions : Traditional outcome variables include self-efficacy, resilience, and skill development, which are achieved through intentionally designed experiences based in different theoretical frameworks.Implications : Outdoor and experiential organizations should consider adapting a broader range of outcome variables in program offerings to address the changing needs of a post-pandemic society.